Influence of Specific Collagen Peptides and Concurrent Training on Cardiometabolic Parameters and Performance Indices in Women: A Randomized Controlled Trial - Jendricke, Patrick; Kohl, Jan; Centner, Christoph; Gollhofer, Albert; König, Daniel (Frontiers in Nutrition, 2020)
The purpose was to examine the effects of concurrent training (CT) combined with specific collagen peptides (SCP) intake on cardiometabolic parameters and performance indices in women. In a double-blind, placebo-controlled, randomized trial recreationally active women (n = 59) completed a 12-week CT training (3 day/week) and ingested 15 g of SCP (treatment group [TG]) or placebo (control group [CG]) on a daily basis. Running distance as a marker of endurance performance (time trial), velocity and heart rate at the lactate and anaerobic threshold (incremental running test) and body composition (bioelectrical impedance analysis [BIA]) were measured. BIA measurements included determination of fat mass (FM) and fat free mass (FFM). Additionally, muscular strength (one-repetition-maximum [1RM]) and muscular endurance (60% of 1RM) were assessed. After 12-weeks, TG had a higher increase in running distance (1,034 ± 643 m) compared to the CG (703 ± 356 m) indicated by a significant interaction effect (p < 0.05). Velocity at lactate and anaerobic threshold improved in both groups over time (p < 0.001), with no significant differences between groups. Similarly, heart rate at lactate threshold decreased over time (p < 0.001), with no time × group interaction. TG declined more in heart rate at anaerobic threshold (−8 ± 14 bpm) than the CG (−1 ± 7 bpm), which resulted in a significant interaction effect (p < 0.01). FM decreased over time in TG and CG (p < 0.001), with no group differences. On contrary, TG had a higher increase in FFM (0.8 ± 0.9 kg) compared to the CG (0.3 ± 1.0 kg) (time × group interaction: p < 0.05). Both, 1RM and muscular endurance improved over time (p < 0.001), with no significant group differences. In conclusion, supplementation of SCP in combination with CT resulted in a significant increase in endurance performance compared to the control group. This might potentially be a consequence of improved structural and cardiometabolic adaptations.